The effect of pending feedback on the IELTS speaking test result: grammatical range and accuracy in focus - Zahra Zargaran (Australian Journal of Applied Linguistics)
Providing feedback on EFL Learners’ speaking errors has been extensively researched, with numerous studies highlighting its benefits. This study investigates the impact of "pending feedback”, a type of feedback where students are required to independently discover the correct answer. Sixty IELTS learners, 30 learners in the experimental group and 30 learners in the control group, were recruited and divided into experimental and control groups, both of which exhibited similar results in the pre-test. The experimental group received pending feedback, while the control group received other types of feedback methods preferred by the teacher but not pending feedback. To find any possible significant difference in group’s performance, and to detect the relation between pending feedback frequency of occurrence and the increased speaking scores in the experimental group, an Independent Sample T-tests and R-Square correlation were conducted on two groups of participants. It was found experimental group demonstrated an improvement in IELTS speaking scores, indicating a strong correlation between pending feedback and better speaking performance. Additionally, the frequency of pending feedback was examined within the experimental group, further confirming that students who received more frequent pending feedback opportunities indicated enhanced performance.